POLITENESS MAXIM OF CHARACTER’S UTTERANCES IN WUTHERING HEIGHTS NOVEL BY EMILY BRONTHE - AMALLYANNA RAMADHINI; Zainuddin Zainuddin (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
This study was aimed at identifying the types and the dominant type of the Politeness Maxim of Character’s Utterances in Wuthering Heights Novel by Emily Bronthe and the reason why it used in the novel. This study was conducted by applying descriptive qualitative method. The source of data was taken from a novel written by Emily Bronthe entitled Wuthering Heights. The results showed that there are 6 types of politeness maxim namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim totalling 64 utterances with the dominant type is agreement maxim totalling 22 utterances (34,37%). There was only 1 type of politeness maxim that not used in the novel which is modesty maxim. The reason why politeness maxim used by the main character was that to politely express his message and intimate the relation to other characters.